(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The innovation of internet has caused confrontations on conventional way of purchasing. At this moment of time online shopping is growing rapidly due to the increasing number of internet users. Notwithstanding, the maximums are consumers are using conventional shopping. This study examines the correlation between conventional shopping and online shopping special reference to Meerut city. Accordingly, 188 samples were selected by snowball sampling methods for this study and primary data for this study was collected through questionnaire from the persons who involve in both conventional and online shopping. The data was investigated descriptively using SPSS software and also arithmetic mean model and graphs were used in this study.